Impact of glycemic control with sitagliptin on the 2-year progression of arterial stiffness: a sub-analysis of the PROLOGUE study. Issue 1 (December 2016) - Tomiyama, Hirofumi; Miwa, Takashi; Kan, Kenshi; Matsuhisa, Munehide; Kamiya, Haruo; Nanasato, Mamoru; Kitano, Tomoki; Sano, Hiroaki; Ohno, Jun; Iida, Masato; Sata, Masataka; Yamada, Hirotsugu; et al.
Abstract Background No conclusive evidence has been obtained yet on the significance of the effects of dipeptidyl peptidase-4 (DPP-4 inhibitor) treatment on the arterial stiffness in clinical settings. In addition, the effects of good glycemic control on the arterial stiffness have also not been clarified yet. As a sub-analysis of the PROLOGUE study, we examined the effect of a DPP-4 inhibitor (sitagliptin) on the 2-year progression of the arterial stiffness and also to determine the effect of good glycemic control on the rate of progression of the arterial stiffness. Methods In the PROLOGUE study, the study participants were either allocated to add-on sitagliptin treatment or to continued treatment with conventional anti-diabetic agents. Among the 463 participants of the PROLOGUE study, we succeeded in measuring the brachial-ankle pulse wave velocity (baPWV) at least two times during the 2-year study period in 96 subjects. Results The changes in the baPWV during the study period were similar between the both groups (i.e., with/without staglipitin), overall. On the other hand, when the study subjects were divided into two groups according to the glycemic control status during the study period good glycemic control group (GC) = hemoglobin (Hb)A1c <7.0 at both 12 and 24 months after the treatment randomization; poor glycemic control group (PC) = HbA1c ≥7.0 at either 12 months, 24 months, or both, the 2-year increase of the baPWV was marginally significantly larger in the PC group (144 ± 235 cm/s) as compared to that the GC group (−10 ± 282 cm/s) (p = 0.036). Conclusion While the present study could not confirm the beneficial effect of sitagliptin per se on the arterial stiffness, the results suggested that good glycemic control appears to be beneficial for delaying the annual progression of the arterial stiffness. Trial registration University Hospital Medical Information Network Clinical Trials Registry UMIN000004490